Introduction - Oxford Energy Forum – Issue, 99 - Fattouh, B (Oxford Institute for Energy Studies, 2015)
This issue of the Oxford Energy Forum is dedicated to Energy in India. Set against the landscape of an uncertain international energy market and a potential slowing of China’s economic growth, the Indian economy stands poised as a hopeful prospect (the IMF forecasts growth of 6.3 per cent in 2015) in an otherwise unsteady global economic recovery. However, India’s new government, elected last May, faces significant challenges in implementing energy reforms, given the complex intertwining of physical (supply), fiscal, poverty and environmental issues. This issue draws together key debates on Indian energy.